Learning Guidance on Logarithms to Improve Students' Mathematical Competence at Mas DDI Baru Baru Tanga - Yonathan S Pasinggi; Abdul Majid; Ritha Tuken; Yulia; Fahirah (PT. TAKAZA INNOVATIX LABS, 2025)
This community service activity aims to improve students' mathematical competency through learning assistance on logarithms at MAS DDI Baru Baru Tanga. Based on initial observations, students experienced difficulties in understanding the basic concepts of logarithms, especially in relating exponential forms to logarithmic forms and their application in everyday life. To address this, the implementation team provided assistance using the Contextual Teaching and Learning (CTL) approach and the Problem Based Learning (PBL) method. The activity involved 25 grade XI IPA students and was carried out over two weeks. The learning process was carried out interactively through discussions, contextual problem solving, and the use of simple digital learning media. Evaluation results showed a significant improvement in student learning outcomes, with the average score increasing from 55.4 to 81.2 after the assistance activity. In addition, student motivation and participation in learning also increased as seen from their activeness throughout the process. This activity succeeded in fostering better conceptual understanding and a positive attitude towards mathematics. This kind of assistance is expected to be implemented sustainably and expanded to other mathematics materials to improve the quality of learning in schools